Issues of the Involvement of Officers in Administrative Responsibility for Committing an Administrative Offense Provided By Part 4.1 of Article 7.30 of the Russian Federation Code on Administrative Offenses - S. M. Rukavishnikov (Сибирское юридическое обозрение, 2021)
The regulatory standards of the legislation on the contractual system in the field of procurement and legislation on the protection of competition are provided with the protective norms enshrined in the Code of the Russian Federation on Administrative Offenses. Sometimes in the disposition of one protective norm, the requirements established by different branches of law can be combined. One such example is Part 4.1 of Art. 7.30 of the Code of the Russian Federation on Administrative Offenses.In the legislation on the protection of competition, for cases of procurement of goods, works, services in order to meet state and municipal needs, there is a prohibition on the inclusion of goods, works, services that are  technologically and functionally unrelated to each other in one lot, if such an action leads to limit competition. The specifics of bringing persons to administrative responsibility under Part 4.1 of Art. 7.30 of the Code of the Russian Federation on Administrative Offenses for violation of this  prohibition in the scientific literature did not receive proper coverage. A  feature of the proceedings in cases of administrative offenses under Part 4.1 of Art. 7.30 of the Code of the Russian Federation on Administrative Offenses is the absence of definitions of the concepts of “functional communication” and “technological communication”. Uncertainty of concepts creates a situation where the border between illegal and lawful actions is very  conditional, which causes cases of unjustified bringing persons to  administrative responsibility.Part 4.1 of Art. 7.30 of the Code of the Russian Federation on Administrative  Offenses also provides for administrative responsibility for the inclusion in  the description of the object of the procurement of requirements and  instructions regarding trademarks, service marks, trade names, patents, utility models, industrial designs, appellation of origin of goods or manufacturer's name, requirements for goods, information, works , services, provided that such requirements entail a limitation of the number of participants in the procurement, with the exception of cases provided for by the legislation of the Russian Federation on the contractual system in the field of procurement. This prohibition is established in the legislation on the contractual system in the field of procurement.An analysis of law enforcement practice indicates that in a number of cases, officials were brought to administrative responsibility without proving the conditions established in Part 4.1 of Art. 7.30 of the Code of the Russian Federation on Administrative Offenses that such requirements of the customer entail a limitation of the number of participants in the procurement.According to the results of the study, the shortcomings of the text of the protective norm in Part 4.1 of Art. 7.30 of the Code of the Russian Federation on Administrative Offenses, proposals were made to amend the Code of the  Russian Federation on Administrative Offenses. The Author points out the  need for a normative definition of the definitions of the concepts “functional connection” and “technological connection”.